Perangkat Pembelajaran Fisika Model Project Based Learning (PJBL) untuk Meningkatkan Keterampilan Proses Sains SMA - Astutik, Fitriyah Ika; Nur, M; Prastowo, T (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
The aim of this research is to produce a physics learning package using Project Based Learning (PjBL) model that valid to increase students science process skill. This research was conducted using these stages from 4-D model, which are defining, designing and developing. Learning package tested in 11st grade of Islamic An-Nidhomiah Senior High School in odd semester of academic year 2017/2018. Learning tools developed which include (a) Syllabus, (b) Lesson Plan, (c) Student Book, (d) Worksheet, and (e) Sheet Assesment. Parameter measured were the validity of package learning with Project Based Learning (PjBL) model. The research data obtained through the validation method. The result of the research showed that the category of learning package developed is valid. Based on the analysis and discussion concluded that the learning package developed were valid.v